Pharmacological Inhibition of Serine Proteases to Reduce Cardiac Inflammation and Fibrosis in Atrial Fibrillation - Coppini, Raffaele; Santini, Lorenzo; Palandri, Chiara; Sartiani, Laura; Cerbai, Elisabetta; Raimondi, Laura (Frontiers in Pharmacology, 2019)
Systemic inflammation correlates with an increased risk of atrial fibrillation (AF) and thrombogenesis. Systemic inflammation alters vessel permeability, allowing inflammatory and immune cell migration towards target organs, including the heart, and also favoring the colonization of the pericardial layer by adipose cells, which represents an additional risk factor for AF. This chemiotactic invasion is likely implicated in short and long term changes in cardiac cell-to-cell communication and in triggering fibrous tissue accumulation in the myocardium and electrophysiological re-arrangements of the cardiomyocytes. Among inflammatory cells infiltrating the heart and/or the annexed adipose pad, macrophages and mast cell have recently attracted the interest of basic researchers due to the pathogenic mechanisms triggered by their secretome, which includes serine proteases. Serine proteases are a large and heterogeneous class of proteases involved in several processes that are important for cardiac function and are involved in cardiac diseases, such as (i)coagulation, (ii)fibrinolysis, (iii)extracellular matrix degradation, (iv)activation of receptors (i.e. proteases activated receptors; PPARs), and (v) modulation of the activity of endogenous signals. The recognition of serine proteases substrates and their involvement in inflammatory/pro fibrotic mechanisms allowed the identification of novel cardio protective mechanisms for commonly used drugs that inhibit serine proteases. The aim of this review is to summarize knowledge on the effects of drugs inhibiting serine proteases in reducing cardiac inflammation thus modulating myocardial fibrosis and AF substrate. These include thrombin and factor Xa inhibitors (used as oral anticoagulants), dipeptidyl-peptidase 4 (dpp4) inhibitors, used for type-2 diabetes, as well as novel experimental inhibitors of mast cell chymases. We will also focus on the interaction of serine protease inhibitors with pericardial adipose cells and how they might modulate their role as determinants of arrhythmic risk in patients with atrial fibrillation.